Capacity Building Sebagai Prakondisi dan Langkah Strategis bagi Perwujudan Otonomi Daerah di Indonesia - Yeremias T Keban (Magister Administrasi Publik, 1999)
Local government autonomy in development has not been successfully materialized in Indonesia although there has been a policy breakthrough with the stipulation of new acts on decentralisation or local government. It is explained that the new acts implementation is still constrained by: 1) strategic failure in implementing local autonomy, 2) misconception about decentralisation and governance autonomy, 3) different perspectives among the political elites, 4) strong grip of centralised bureaucracy, and 5) the loose control from the legislatives and the public at large. It is also argued that local government have to deal with such constraints because the lack of capability to administer development in a decentralised context which implies that capacity building is extremely urgent for the local autonomy. Furthermore, capacity building for the local government officials can only be accomplished if there is an appropriate approach and strategy. This article recommends some practical guidance for the capacity building programmes to meet the requirement, namely: 1) strategic intervention, 2) institutional building, 3) action programme, and 4) continual improvement. At the bottom line, all the capacity building programmes should be able to convince the local government officials about the importance of local government vision for development, human resources improvement, local institutions' revitalisation, organisational networking, and understanding the context of local development.